An equilibrium analysis of optimal audit contracts* - MELUMAD, NAHUM; THOMAN, LYNDA (Contemporary Accounting Research, 1990)
The nature of optimal equilibrium contracts for auditors hired by firms to certify the validity of firms' financial reports is studied in this paper. Financial reports may affect the interest rates at which firms can borrow funds; hence, without auditing, firms might be inclined to present favorable, if not altogether accurate, financial information. We observe that an optimal audit contract that allows auditors' contracts to be contingent on the audit report can take different forms depending on the parameter values; only in rare cases is an optimal contract independent of the audit report. Specifically, in some cases, an optimal contract is characterized by a payment for a favorable report that is larger than the payment for an unfavorable report. In other cases, the conclusion is reversed. We note, in contrast to the spirit of agency models, that an audit contract need not function in equilibrium as a motivational device inducing the auditor to work; in some cases, it serves as a means to transfer signaling costs from low‐risk firms to high‐risk firms. We also provide a rationale for mandating noncontingent audit contracts. In some circumstances equilibria in which auditing is informative cannot exist when contingent contracting is allowed; once contracts are required to be noncontingent, however, there exist equilibria in which auditing is informative. Résumé. Les auteurs étudient la nature des contrats d'équilibre optimaux relatifs aux services de vérificateurs visant l'attestation de la validité des états financiers des entreprises. Les rapports financiers peuvent influer sur les taux d'intérêt auxquels les entreprises peuvent emprunter; sans la vérification, les entreprises pourraient donc avoir tendance à présenter de l'information qui leur est favorable, faute d'être absolument exacte. Les auteurs remarquent qu'un contrat de vérification optimal conditionnel au contenu du rapport du vérificateur peut revêtir diverses formes, selon la valeur des paramètres; ce n'est qu'en de rares cas que le contrat optimal n'est pas conditionnel au rapport des vérificateurs. De façon spécifique, la rétribution est parfois plus élevée pour un rapport favorable que pour un rapport défavorable. Dans d'autres cas, c'est le contraire qui se produit. Les auteurs notent que contrairement au principe des modèles mandant‐mandataire, il n'est pas nécessaire que le contrat de vérification se trouve en situation d'équilibre pour servir à la motivation du vérificateur; dans certains cas, il sert de mécanisme de transfert des coûts « indicateurs » des entreprises présentant un faible risque aux entreprises ayant un risque évevé. Les auteurs exposent également les principes de l'adjudication de contrats de vérification non conditionnels. Dans certains contextes, les équilibres pour lesquels la vérification est informative ne peuvent exister si l'on permet que les contrats soient conditionnels; dès qu'on exige que les contrats soient non conditionnels, cependant, on obtient des équilibres pour lesquels la vérification est informative.